EFEKTIVITAS SIDANG KELILING TERHADAP PENERAPAN ASAS, SEDERHANA, CEPAT DAN BIAYA RINGAN - Nur Ita Wahyuni; Halim Talli; Muhammad Fajri (Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract This study discusses the effectiveness of the trial on the application of simple, fast and low-cost principles (a case study of the settlement of the isbat marriage case at the Bulukumba Religious Court). This study aims to find out how effective the mobile court is in the marriage isbat case and how it is applied as a simple, fast and cost-effective case in the settlement of marriage isbat cases through a mobile trial at the Bulukumba Religious Court. This research is qualitative in nature where the data collection is in the form of field reports or according to facts in the field. The approach used is the Juridical Empirical approach with data collection methods, namely documentation and interviews. The results showed that the mobile court in the settlement of the isbat marriage case at the Bulukumba Religious Court was calculated in terms of distance, implementation procedures to settlement of cases and fulfilled the 5 indicators of effectiveness according to Soerjono Soekanto. The application of the principle of justice has been carried out well, starting from the implementation which is not complicated and the costs incurred are only the down-payment costs of the case. Keywords: Effectiveness, Circuit Court, Judicial Principles, Marriage Isbat.